FAKTOR-FAKTOR YANG MEMPENGARUHI STUNTING DI PUSKESMAS SAITNUHUTA - Sinaga, Gunawan Parlindungan; Sinaga, Jon Piter; Ginting, Selamat (Jurnal Penelitian Kesmasy, 2024)
Stunting is a condition in which a child's physical growth does not reach the height that is appropriate for his age is known as stunting. This suggests that the child is experiencing growth delays, which can hinder his physical and mental development. Stunting occurs when children aged 12 to 59 months and younger experience growth failure as a result of chronic malnutrition, particularly during the first 1,000 days of life. Thus, kids have a level that is more limited than the standard that ought to be as per their age. Nine children in the Saitnihuta Community Health Center's Doloksanggul District working area were stunted out of 93 samples of children under the age of five. This study aims to identify the factors that contribute to the preval___ence of stunting in the Doloksanggul District's Saitnihuta Community Health Center working area. This kind of research is quantitative and uses a cross-sectional approach and a survey design. The example for this exploration was 93 examples. Univariate, bivariate and multivariate information handling examination. Bivariate examination with chi-square test and multivariate investigation with different calculated relapse. The consequences of this examination are that there is a connection between work (p esteem = 0.027), instruction (p esteem = 0.004), information (p esteem = 0.000), nurturing style (p esteem = 0.012) and disposition (p esteem = 0.007) with hindering . The predominant variable connected with hindering is information. Scientists propose that local area wellbeing focuses can expand the information and knowledge of moms to comprehend the significance of keeping hindering from the age of five to diminish the frequency of hindering in Indonesia, Saitnihuta People group Wellbeing Center, Doloksanggul Region. Key words: stunting, work, education, knowledge, parenting patterns, attitudes